School Entry, Compulsory Schooling, and Human Capital Accumulation: Evidence from Michigan - Steven W. Hemelt; Rachel B. Rosen (Institute for the Study of Labor (IZA), 2016)
Extant research on school entry and compulsory schooling laws finds that these policies increase the high school graduation rate of relatively younger students, but weaken their academic performance in early grades. In this paper, we explore the evolution of postsecondary impacts of the interaction of school entry and compulsory schooling laws in Michigan. We employ a regression-discontinuity (RD) design using longitudinal administrative data to examine effects on high school performance, college enrollment, choice, and persistence. On average, we find that children eligible to start school at a relatively younger age are more likely to complete high school, but underperform while enrolled, compared to their counterparts eligible to start school at a relatively older age. In turn, these students are 2 percentage points more likely to first attend a two-year college, and enroll in fewer postsecondary semesters, relative to their older counterparts. We explore heterogeneity in these effects across subgroups of students defined by gender and poverty status. For example, we illustrate that the increase in the high school graduation rate of relatively younger students attributable to the combination of school entry and compulsory schooling laws is driven entirely by impacts on economically disadvantaged students.
Keywords: I20; I21; I28; 330; school entry; compulsory schooling; postsecondary enrollment